A intermediação do trabalho humano por meio de tecnologias algorítmicas e a necessidade de proteção do trabalhador: os desafios de adequação do corpus jurídico-trabalhista às novas modalidades de exploração do trabalho na era digital - Wanessa Mendes De Araújo (2019)
This paper discusses platform capitalism - understood as a new business model that uses the electronic intermediation of the provision of services to organize the production and regiment the workforce-, in order to understand and analyze how these new contractual arrangements have repercussions on Labor Law. The research studied the business models constituted through digital platforms, under lucrative orientation and demonstrated that, despite the existence of a common substratum to all of them, technological companies, have wide powers to dispose on their selfregulation and on their form of operation, which gives them their own identity and, in many cases, defies consolidated state norms. The present study revealed the new mechanisms of interference by technological companies on human work to demonstrate that some digital platforms use these sophisticated methods to actively manage and discipline the provision of services without the need to issue orders. This dissertation demonstrates that, in the case of digital platforms for labor intermediation with a lucrative purpose, behind rhetorical landmarks of work with independence and freedom, what is found is a manifest and deliberate action of the companies aimed at minimizing responsibilities entrepreneurs through the escape of labor law, to the detriment of the worker, every day more vulnerable and helpless, impelled to accept precarious work, of very short duration and with uncertain provisions. The research adopts the juridical-sociological methodological aspect, having as theoretical technique the research in comparison with jurisprudential analysis, being the type of research selected the legal-comprehensive.